REVIEW ON THE RISK ASSESSMENT TO DETERMINE GUARANTEE FEE STANDARDIZATION(CASE STUDY: PT ALAM ENERGI, JAKARTA) - Astarini, Nadira
This final project includes a complete analysis of building a risk assessment-driven guarantee fee structure, focusing on PT Alam Energi as a case study. The study addresses the crucial need for a systematic way to determine guarantee fees that appropriately reflect the related risks while maintaining fairness and openness. Infrastructure development is critical for Indonesia's economic growth, and stateowned companies (SOEs) such as PT PII play an essential role. However, present methods for calculating guarantee fees are inconsistent and lack an organized methodology, resulting in lengthy negotiations and potential biases. This study intends to close this gap by creating a standardized methodology based on a thorough literature analysis and risk assessment factors such as credit rating, financial health, loan tenure, guarantee coverage, project complexity, historical performance, and contingency planning. The technique is divided into three stages: a broad literature review serves as the theoretical underpinning for the framework, followed by the creation of a risk evaluation system. The approach is applied by analyzing quantitative data from PT Alam Energi's Project A and financial and operational data from PT PII. The US Index Theory, which uses financial characteristics to analyze loan sustainability, improves the risk assessment. Each criterion is weighted based on its relative value, using the Simple Multi-Attribute Rating Technique (SMART) to achieve a fair ii rating. The methodology is then validated by applying it to PT Alam Energi Project A, demonstrating its practical utility. Applying the framework to PT Alam Energi's Project A yields many noteworthy discoveries. First, the framework establishes a standardized system for evaluating and calculating guarantee fees, which aligns with industry best practices while decreasing the subjectivity and inconsistencies of present approaches. Second, including precise risk evaluation criteria ensures that all relevant elements are addressed, resulting in a more accurate and equitable assessment of project hazards. Third, the framework's real-world use demonstrates its potential for applicability to other infrastructure development sectors. These findings illustrate the framework's capacity to calculate guarantee fees transparently and equitably while accurately reflecting the project's risk profile. The study suggests that a risk assessment-driven guarantee fee structure improves the fairness and transparency of fee determinations, consequently increasing the financial sustainability and effectiveness of PT PII's guarantee mechanisms. Adopting this paradigm will streamline the fee-setting process, eliminate administrative overhead, and ensure that all SOEs are treated equally. Furthermore, the study recommends that future research focus on improving and verifying the framework across various project kinds and sectors to enhance its generalizability and robustness. This framework is designed to benefit PT PII and its stakeholders while contributing to the larger aims of national infrastructure development and economic growth by ensuring that financial resources are distributed efficiently and risks are appropriately managed. Finally, this final project contributes significantly to the field of infrastructure finance by establishing a robust and risk-based framework for guarantee fees. The application to PT Alam Energi's Project A is a good case study demonstrating the framework's efficacy and practicality. This study's findings can potentially affect policy and practice in managing financial guarantees for infrastructure projects, thereby encouraging long-term economic development in Indonesia